The Consensus from the Mycobacterium avium ssp. paratuberculosis (MAP) Conference 2017 - Kuenstner, J. Todd; Naser, Saleh; Chamberlin, William; Borody, Thomas; Graham, David Y.; McNees, Adrienne; Hermon-Taylor, John; Hermon-Taylor, Amy; Dow, C. Thomas; Thayer, Walter; Biesecker, James; Collins, Michael T.; et al. (Frontiers in Public Health, 2017)
On March 24 and 25, 2017 researchers and clinicians from around the world met at Temple University in Philadelphia to discuss the current knowledge of Mycobacterium avium ssp. paratuberculosis (MAP) and its relationship to human disease. The conference was held because of shared concern that MAP is a zoonotic bacterium that poses a threat not only to animal health but also human health. In order to further study this problem, the conferees discussed ways to improve MAP diagnostic tests and discussed potential future anti-MAP clinical trials. The conference proceedings may be viewed on the www.Humanpara.org website. A summary of the salient work in this field is followed by recommendations from a majority of the conferees.